Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(=4x^2-25-4x^2+12x-9-12x=-34\)
b: \(=8y^3-12y^2+6y-1-2y\left(4y^2-12y+9\right)-12y^2+12y\)
\(=8y^3-24y^2+18y-1-8y^3+24y^2-18y=-1\)
c: \(=x^3+27-x^3-20=7\)
d: \(=3y\left(9y^2+12y+4\right)-27y^3+1-36y^2-12y-1\)
\(=27y^3+36y^2+12y-27y^3-36y^2-12y\)
=0
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 45: (SBT/12):
a. (5x4 - 3x3 + x2) : 3x2
= (5x4 : 3x2) + (-3x3 : 3x2) + (x2 : 3x2)
=\(\dfrac{5}{2}\)x2 - x + \(\dfrac{1}{3}\)
b. (5xy2 + 9xy - x2y2) : (-xy)
= [5xy2 : (-xy)] + [9xy : (-xy)] + [(-x2y2) : (-xy)]
= -5y - 9 + xy
c. (x3y3 : \(\dfrac{1}{3}\)x2y3 - x3y2) : \(\dfrac{1}{3}\)x2y2
= (x3y3 : \(\dfrac{1}{3}\)x2y2) + (-\(\dfrac{1}{2}\)x2y3 : \(\dfrac{1}{3}\)x2y2) + (-x3y2 : \(\dfrac{1}{3}\)x2y2)
= 3xy - \(\dfrac{3}{2}\)y - 3x
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 6x2.(3x2 - 4x + 5) = 18x4 - 24x3 + 30x2
b) (x - 2y)(3xy + 6y2 + x) = 3x2y + 6xy2 + x2 - 6xy2 - 12y3 - 2xy = -12y3 + 3x2y - 2xy + x2
c) (18x4y3 - 24x3y4 + 12x3y3) : (-6x2y3) = -6x2y3(-3x2 + 4xy - 2x) : (-6x2y3) = 4xy - 3x2 - 2x
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(=\dfrac{27a^6b^3\cdot a^2b^6}{a^8b^8}=27b\)
b: \(=3y^2-5x^2y^3-2y^2+3x^2y^3\)
\(=y^2-2x^2y^3\)
c: \(=6x-y+2x^2+3y-2x^2+x\)
\(=7x+2y\)
d: \(=x-y+2y^2-6xy+\dfrac{10x^2}{y}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(5x^2y^4:10x^2y=\dfrac{1}{2}y^3\)
c: \(\left(-xy\right)^{10}:\left(-xy\right)^5=-x^5y^5\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(=3y^2-5x^2y^3-2y^2+3x^2y^3=y^2-2x^2y^3\)
b: \(=6x-y+2x^2+3y^2-2x^2+x=7x-y+3y^2\)
c: \(=x-y+4y^2-6xy+\dfrac{10x^2}{y}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a.\left(9x^2y^3-15x^4y^4\right):3x^2y-\left(2-3x^2y\right)y^2\)
\(=3y^2-5x^2y^3-2y^2+3x^2y^3\)
\(=y^2-2x^2y^3\)
\(b.\left(6x^2-xy\right):x+\left(2x^3y+3xy^2\right):xy-\left(2x-1\right)x\)
\(=6x-y+2x^2+3y-2+x\)
\(=2x^2+7x+2y-2\)
\(c.\left(x^2-xy\right):x+\left(6x^2y^5-9x^3y^4+15x^4y^3\right):\dfrac{3}{2}x^2y^3\)
\(=x-y+4y^2-6xy+10x^2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a/ (\(x^3y^2\)-\(\frac{1}{2}x^3y\) + \(2xy\) - \(2x^2y^3\) + \(xy^2\) - \(4y^2\) =
`a, (x+2y)^3 = x^3 + 6x^2y + 12xy^2 + 8y^3`
`b, (3y-1)^3 = 27y^3 - 27y^2 + 3y-1`
`a)`
`(x + 2y)^3`
`= x^3 + 6x^2y + 12xy^2 + 8y^3`
`b)`
`(3y - 1)^3`
`= 27y^3 - 27y^2 + 9y - 1`